Brand resonance and customer loyalty in the banking sector: A study of the lower mass market - Zulu, Zinhle (University of the Witwatersrand, Johannesburg, 2022)
This research had its focus on investigating the influential elements of brand resonance and the customer value proposition in driving customer brand loyalty. The qualitative study set out to uncover a broad array of sub-topics that are associated with qualities of the customer value proposition that drive brand resonance that leads to brand loyalty in the Living Standard Measure (LSM) 2-5 market segment of the banking market. To get to the essence of the study, key management constructs were explored, namely the Theory of Reciprocity and Keller’s Brand Equity Model to explore characteristics that drive brand love. Being exploratory in form, the analysis was steered by a qualitative design. Interrogative interviews were carried out with an appropriate sample to gain well-informed and representative insight on this topic. In a Volatile, Uncertain, Complex, Ambiguous (VUCA) world where household income is burdened, customers place more importance on value, quality, and emotional brand connections, and how these correlate with each other to realise brand loyalty. Findings of the study revealed that the lower mass market’s comprehension of brand resonance and value proposition is limited to colour and the cost of banking. It was, however, evident there is broader subconscious understanding but how it translates in the physical is circumstantial
A research report submitted in partial fulfillment of the requirements for the degree of Master’s in Business Administration to the Faculty of Commerce, Law and Management, Wits Business School , University of the Witwatersrand, Johannesburg, 2022
Keywords: Brand resonance; Brand loyalty; Brand identity; Theory of reciprocity; Brand meaning; Customer value proposition; UCTD; SDG-8: Decent work and economic growth